History of Canadian Geology:: The Scintillation Counter: Its Early Application as a Geophysical Instrument - Brownell, George (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1974)
Summary The portable scintillation counter as first used in prospecting for uranium was a distinctly Canadian invention, as was also the portable geiger counter which preceeded it- Its use as a geophysical instrument was an instant success. The Canadian Patent Office was at that time inundated with patent applications on improvements in ionization chambers and geiger counters but with the advent of the scintillation counter most applications concerning counters using gas in their detecting process ceased abruptly, they were obsolete. With a counting rate a hundred times or more above that of gas counters and its ability to discriminate gamma ray energy, the scintillation counter was quickly adopted for oil well logging, airborne and ground radioactivity surveys as well as expanded scientific research and medical applications. Much of the rapid advance in the field of radioactivity since 1950 is due to the scintillation counter.